Strengthening Anti-Corruption Governance through Information Technology: Developing a Digital Transparency Model Based on Islamic Civil Society Organizations in Batu City - Tinuk Dwi Cahyani; Muhamad Helmi Md Said; Grace Emmanuel Kaka; Yaoyao Li; Nabila Aprilia Rismara (Kosmik Hukum, 2026)
This study explores the anti-corruption movement initiated by Islamic organizations through the utilization of information technology systems in Batu City. Challenges in implementing such systems include limitations in infrastructure, human resources, and regulatory frameworks, leading to regional disparities and digital divides. Furthermore, bureaucratic complexity and institutional resistance often impede the optimal use of technology to promote transparency and accountability. Employing both normative and empirical legal research methods, this study integrates a statute approach and a case approach to analyze relevant legal frameworks and real-world practices. Data were collected through Focus Group Discussions (FGDs) with the two largest Islamic organizations in Batu City, Nahdlatul ‘Ulama Branch Leadership (PCNU) and the Muhammadiyah Regional Leadership (PDM) as well as from policy documents and field observations. NVivo 12 Plus software was used to systematically code qualitative data, identify themes related to transparency, accountability, and corruption prevention, and visualize interconnections among findings. The results reveal that both organizations play a strategic role in supervising local governance. PDM Batu City actively conducts research on corruption issues and formulates policy recommendations to strengthen public integrity, while PCNU Batu City promotes a multidisciplinary approach that involves academics and the private sector in policy development. Despite the absence of integrated online financial management systems in schools under these organizations, their commitment to adopting digital platforms indicates progress toward enhanced transparency and data reliability. Overall, Islamic organizations contribute significantly to fostering anti-corruption values through technology-based governance initiatives in Batu City.